2005
DOI: 10.1182/blood-2005-03-1033
|View full text |Cite
|
Sign up to set email alerts
|

Effective therapy of human lymphoma xenografts with a novel recombinant ribonuclease/anti-CD74 humanized IgG4 antibody immunotoxin

Abstract: Ranpirnase (Rap) is a cytotoxic ribonuclease (RNase) isolated from frog oocytes. Here we describe high antitumor activity of a novel immunotoxin, 2L-Rap-hLL1-␥4P, composed of 2 Rap molecules, each fused to the N terminus of the light chain of hLL1, an internalizing anti-CD74 humanized antibody. To reduce unwanted side effects, the constant region of hLL1 was changed from ␥1 to ␥4 and further to ␥4P by replacing serine 228 to proline to prevent the formation of a half immunoglobulin G (IgG) common for IgG 4 . I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…In vivo, the pharmacokinetic profile of 2L-RaphLL1-g4P was similar to that of hLL1. Most importantly, marked therapeutic efficacy was shown in animal models of (62). Figure 6 summarizes a study in which Rap-hLL1 specifically targeted Daudi xenografts and yielded long-term survival in all treated mice.…”
Section: Drug and Toxin Antibody Conjugatesmentioning
confidence: 99%
“…In vivo, the pharmacokinetic profile of 2L-RaphLL1-g4P was similar to that of hLL1. Most importantly, marked therapeutic efficacy was shown in animal models of (62). Figure 6 summarizes a study in which Rap-hLL1 specifically targeted Daudi xenografts and yielded long-term survival in all treated mice.…”
Section: Drug and Toxin Antibody Conjugatesmentioning
confidence: 99%
“…The construction of the plasmid pdHL2-Rap-L-hLL1-γ4P for expressing 2L-Rap-hLL1-γ4P has been described in detail (9). The expression vector pdHL2-Rap (Q)-LhLL1-γ4P was derived from pdHL2-Rap-L-hLL1-γ4P by replacing Rap with Rap(Q), and the plasmid pdHL2-Rap (Q)-L-hRS7-γ1 for expressing (Q)-hRS7 was constructed by subcloning Rap(Q) gene from pdHL2-Rap(Q)-L-hLL1-γ4P into pdHL2-hRS7-γ1 vector.…”
Section: Vector Constructionmentioning
confidence: 99%
“…We have previously reported that 2L-Rap-hLL-γ4P retained the binding affinity and specificity for CD74 when compared with unconjugated hLL1, displayed RNase activity comparable with free Rap, showed potent in vitro cytotoxicity against CD74-positive (Daudi, Raji, and MC/CAR), but not CD74-negative (DMS 53), cell lines, and showed an excellent therapeutic index in vivo in two xenograft models of non-Hodgkin lymphoma (9). In this work, we provide a further example to illustrate that the NH 2 -terminal fusion of Rap(Q) to a tumortargeting mAb is a valid and versatile approach to generate novel immunotoxins by showing that (Q)-hRS7 (a) can be produced in a mammalian host and purified to homogeneity, (b) retains the binding specificity and affinity of hRS7, as well as the RNase activity of Rap, (c) suppresses the proliferation of various Trop-2-expressing cancer cell lines at nanomolar concentrations in vitro, and (d) inhibits the growth of a human lung tumor xenograft in vivo.…”
Section: Introductionmentioning
confidence: 97%
“…Fab' internalization occurs just as rapidly as immunoglobulin G (IgG) binding, indicating that bivalent binding is not required (3,10). Later studies with a complementarity-determining region (CDR)-grafted version of murine LL1, milatuzumab (hLL1), found that the antibody could alter B-cell proliferation, migration, and adhesion molecule expression (8,11,12), but the exceptional internalization properties of the anti-CD74 antibody made it an efficient carrier for the intracellular delivery of cancer therapeutics (13)(14)(15)(16). On the basis of preclinical efficacy and toxicology results, phase I clinical trials with milatuzumab in multiple myeloma (17), as well as milatuzumab-doxorubicin in multiple myeloma, non-Hodgkin lymphoma, and chronic lymphocytic leukemia, have been initiated.…”
Section: Introductionmentioning
confidence: 99%